Effect of Self-Instruction Technique on Social Media Addiction among Secondary School Students in Nnewi North Local Government Area (Journal of Guidance and Counselling Studies, 2024)
This study investigated the effect self-instruction technique on social media addiction among secondary school students in Anambra State. Two research questions and two null hypotheses guided the study. Quasi-experimental research was adopted in carrying out the study. A sample size of 107 male and female SS2 students drawn from three coeducational schools was chosen from a population of 259 that were identified with high social media addiction. The sample was derived from three secondary schools selected using multi-stage sampling procedure based on the number of students that scored high on Social Media Addiction Scale. The Social Media Addiction Scale (SMAS) was used for data collection. The instrument was reliable at 0.83 coefficients. Data relating to research questions were analyzed using statistical mean while data relating to hypotheses were analyzed using Analysis of Co-Variance (ANCOVA). Findings from the study revealed that self-instruction technique was significantly effective in reducing social media addiction among secondary school students. The findings also showed that self-instruction technique was more effective on male secondary school students’ social media addiction than the females. The researcher therefore recommended among others, that Counsellors in secondary schools should use self-instruction technique for their male students, and that the Counselling Association of Nigeria (CASSON) should collaborate with government to ensure that enough qualified counsellors are employed in secondary schools to take adequate care of the students’ psychological needs.
Keywords: Self-Instruction; Technique; Social Media; Addiction; Anambra State